Experimental Analysis of Hybrid UAV at Different Velocities - et. al., S.Mahendran, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The primary goal of this project is to constricting a hybrid UAV with both rotary and flapping wing. The primary objective of this project is to find the Lift in respect to RPM/Frequency in different modes of operation i.e. with operating only the propeller, flapping wing and with both propeller and flapping wing working simultaneously. For finding lift we will be using load cell. we will be studying the effect of a Flapping Wing when placed in Quadcopter and check whether the result have a positive effect or negative effects. The end result show's that there's a minute increase in lift when flapping wing is added to a quadcopter